Home away from home : immigrant narratives, domesticity, and coloniality in contemporary Spanish culture - Murray, N. Michelle (North Carolina studies in the Romance languages and literatures, 2018)
"Home Away from Home: Immigrant Narratives, Domesticity, and Coloniality in Contemporary Spanish Culture examines ideological, emotional, economic, and cultural phenomena brought about by migration through readings of works of literature and film featuring domestic workers. In the past thirty years, Spain has experienced a massive increase in immigration. Since the 1990s, immigrants have been increasingly female, as bilateral trade agreements, migration quotas, and immigration policies between Spain and its former colonies (including the Dominican Republic, Ecuador, Equatorial Guinea, and the Philippines) have created jobs for foreign women in the domestic service sector. These migrations reveal that colonial histories continue to be structuring elements of Spanish national culture, even in a democratic era in which its former colonies are now independent. Migration has also transformed the demographic composition of Spain and has created complex new social relations around the axes of gender, race, and nationality. Representations of migrant domestic workers provide critical responses to immigration and its feminization, alongside profound engagements with how the Spanish nation has changed since the end of the Franco era in 1975. Throughout Home Away from Home, readings of works of literature and film show that texts concerning the transnational nature of domestic work uniquely provide a nuanced account of the cultural shifts occurring in late twentieth- through twenty-first-century Spain."--Publisher description